Genetic profile of two isolates of Trypanosoma evansi from southern Brazil with different parasitaemias - Daniel Pereira Duarte; Larissa Kaori Oide Komati; Kaio César Simiano Tavares; Cícera Regina Lazzarotto; Éden Ramalho de Araújo Ferreira; Diana Bahia; Luiz Claudio Miletti (Biotemas)
Trypanosoma evansi is the most widespread pathogenic trypanosome, due to its ability to be mechanically transmitted by hematophagous flies. Some studies have shown that T. evansi has a high genetic homology among populations around the world, but they have not described the relationships among infection patterns in the host. In this study, we used molecular techniques to determine the genetic variability of two isolates of T. evansi from southern Brazil showing different infection patterns in a murine model. Genetic variability markers were amplified using the techniques described, as well as the presence of DNA from kinetoplast was also checked. We found a very close genetic profile between the isolates of T. evansi using random amplified polymorphic DNA (RAPD) and markers inter-simple sequence repeats (ISSR). Primers derived from the sequence of Trypanosoma brucei maxicircle encoding the subunit 5 of NADH dehydrogenase (nad5) were used to demonstrate the absence of maxicircles, while immunofluorescence was used to check the lack of DNA from kinetoplast. All methods reveal the absence of kDNA, as occurring in American isolates of T. evansi. Perhaps, differences noticed in the phenotypic patterns of animals that were observed during infection are not associated with the molecular changes, but with the adaptation to different hosts, as described for other trypanosomatids.